2014
DOI: 10.1037/cpp0000054
|View full text |Cite
|
Sign up to set email alerts
|

Conducting psychological intervention research in pediatric clinical settings: Strategies and implications.

Abstract: Practice-based psychological intervention research that is conducted by practitioners in pediatric clinical settings raises special challenges that need to be met to maximize opportunity for success. Based on our experiences in intervention research conducted in clinical settings by practicing pediatric psychologists and health care providers, we consider issues in designing and implementing intervention research, resource development, interdisciplinary collaboration, ethical issues, data analysis, and applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Indeed, the only detailed descriptions of a multidisciplinary clinic was reported nearly 2 decades ago; and then only select patients suspected of having comorbid psychopathology were able to access any form of psychosocial treatment (Poenaru et al, 1997). Along these lines, Drotar et al (2014) called for improvements in intervention research in pediatric psychology. They suggested that research on the development of interventions by clinical practitioners in clinical settings is one of the most important directions for research in pediatric psychology with the goal of improving ecological validity and generalization of our treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the only detailed descriptions of a multidisciplinary clinic was reported nearly 2 decades ago; and then only select patients suspected of having comorbid psychopathology were able to access any form of psychosocial treatment (Poenaru et al, 1997). Along these lines, Drotar et al (2014) called for improvements in intervention research in pediatric psychology. They suggested that research on the development of interventions by clinical practitioners in clinical settings is one of the most important directions for research in pediatric psychology with the goal of improving ecological validity and generalization of our treatments.…”
mentioning
confidence: 99%
“…Indeed, Borowitz et al (2002) noted the limitation of carrying out most effective treatments because of “practical time limitations” (p. 383). In support of the desire of Drotar et al (2014) to improve the clinical significance of pediatric psychology research, it is important to disseminate clinical interventions within a multidisciplinary clinic model and determine the achievable outcomes for this common and challenging condition.…”
mentioning
confidence: 99%
“…Additional goals for CPPP included addressing topics related to health care reform policy issues (see Phelps, 2014), professional “real world” practice issues (see Smolyansky, Stark, Pendley, Robins, & Price, 2013), and technology (see Smith et al, 2015). Also, in addition to including articles with direct clinical applications, we offered guidelines to authors regarding how to present case illustrations (Ernst, Barhight, Bierenbaum, Piazza-Waggoner, & Carter, 2013), quality improvement studies (Schurman, Gayes, Slosky, Hunter, & Pino, 2015), and qualitative research (Alderfer & Sood, 2016), as well as strategies for conducting and analyzing research in clinical settings (Drotar et al, 2014; Noser, Cushing, Mcgrady, Amaro, & Huffhines, 2017; Rohan, 2013).…”
mentioning
confidence: 99%
“…Please see this issue for a list of all ad hoc and student reviewers.This year, APA launched a new program, APA Spotlight Program, a program where APA sends summaries of highlighted articles of a subset of journals to targeted audiences. We are pleased that APA chose CPPP for this program, and many of you may have seen the summaries of CPPP articles (e.g., Drotar et al, 2014;Moser, Plante, LeLeiko, & Lobato, 2014). These spotlighted articles will soon be posted on the APA website, http://www.apa.org/pubs/highlights/index .aspx.…”
mentioning
confidence: 99%